2008
DOI: 10.3139/146.101645
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of crystallographic texture due to displacive transformations

Abstract: Displacive transformations involve the disciplined motion of atoms. As a result, there are clearly defined relationships between all aspects of the parent and product lattices. The theory for this is well established but has not been exploited in the calculation of transformation textures. This paper is a critical assessment of the methods for the estimation of crystallographic textures during the displacive transformation of austenite into martensite, bainite or Widmanstätten ferrite in steels. The discussion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…There are important unresolved difficulties in the calculation of crystallographic texture due to displacive transformation under the influence of stress [1,2]. It is often assumed that it is sufficient to plot calculated crystallographic orientations on stereographic projections or similar devices, and then compare against experimental data which contain not only the location of poles but also the associated diffraction intensity.…”
Section: Motivationmentioning
confidence: 99%
“…There are important unresolved difficulties in the calculation of crystallographic texture due to displacive transformation under the influence of stress [1,2]. It is often assumed that it is sufficient to plot calculated crystallographic orientations on stereographic projections or similar devices, and then compare against experimental data which contain not only the location of poles but also the associated diffraction intensity.…”
Section: Motivationmentioning
confidence: 99%
“…32,[34][35][36] The theory predicts that the crystallographic indices representing the orientation relationship and habit plane are in general irrational; that means that the indices cannot be expressed by the division of integers. This necessarily means that there will be 24 variants of the transformation product per austenite grain.…”
Section: )mentioning
confidence: 99%
“…The overall transformation elastic strain tensor can be calculated and compare to the applied stress, resulting in a calculation of which variants are favoured by the applied stress state. [20][21][22][23] Bhadeshia 10 showed that the volume change due to the transformation in bainite is much smaller than the shear component. Babu and Bhadeshia 24 studied the effect of applied stress on the formation of acicular ferrite.…”
Section: Introductionmentioning
confidence: 99%